2018
DOI: 10.1038/s41598-018-22150-x
|View full text |Cite
|
Sign up to set email alerts
|

An allosteric link connecting the lipid-protein interface to the gating of the nicotinic acetylcholine receptor

Abstract: The mechanisms underlying lipid-sensing by membrane proteins is of considerable biological importance. A unifying mechanistic question is how a change in structure at the lipid-protein interface is translated through the transmembrane domain to influence structures critical to protein function. Gating of the nicotinic acetylcholine receptor (nAChR) is sensitive to its lipid environment. To understand how changes at the lipid-protein interface influence gating, we examined how a mutation at position 418 on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 56 publications
2
27
0
1
Order By: Relevance
“…R301, which has the largest effect on desensitization when mutated, is conserved among many mammalian pLGICs including GABA A R and nAchR isoforms, and R299 is adjacent to R301 at the bottom of TM4. Mutations in this region of TM4 have profound effects on pLGIC desensitization (Bouzat et al, 1998; Li et al, 1992; Domville and Baenziger, 2018; Lee et al, 1994). R117 and R123 are located at the extracellular end of TM4, and boundary POPG with headgroups that interact with these residues have acyl chains that make contacts with intrasubunit sites on both sides of TM4 (Figures 8B and 5B).…”
Section: Discussionmentioning
confidence: 99%
“…R301, which has the largest effect on desensitization when mutated, is conserved among many mammalian pLGICs including GABA A R and nAchR isoforms, and R299 is adjacent to R301 at the bottom of TM4. Mutations in this region of TM4 have profound effects on pLGIC desensitization (Bouzat et al, 1998; Li et al, 1992; Domville and Baenziger, 2018; Lee et al, 1994). R117 and R123 are located at the extracellular end of TM4, and boundary POPG with headgroups that interact with these residues have acyl chains that make contacts with intrasubunit sites on both sides of TM4 (Figures 8B and 5B).…”
Section: Discussionmentioning
confidence: 99%
“…A common transmembrane-binding region suggests that perturbation of the transmembrane domains is a critical structural feature needed to potentiate nAChR opening. It is known that nAChR function is very sensitive to conformational changes in the transmembrane domain M4, which directly connects to the C-tail (42,43). Subtle alterations in the tertiary structure of M4 could easily alter the conformation of the C-tail, thereby affecting nAChR function.…”
Section: Discussionmentioning
confidence: 99%
“…Subtle alterations in the tertiary structure of M4 could easily alter the conformation of the C-tail, thereby affecting nAChR function. It was shown that a single C418W mutation in M4 of ␣1 increased sensitivity to ACh by 16-fold (42). M4 is also believed to act as a "lipid sensor" in ␣1 (43).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that M4 interactions with M1 and M3 in some pLGICs are necessary to promote effective interactions between the M4 C-terminus and the Cys-loop, which are located at the interface of the ECD and the TMD, and are important in coupling agonist binding to channel opening [ 19 , 20 ]. It is also possible that there are more direct links, for example W418 in the nAChR M4 α-helix has recently been shown to interact directly with S226 on the adjacent M1 α-helix, stabilizing the open state [ 21 ]. Thus understanding the interactions made by aromatic residues is an important step in understanding the mechanism of activation of pLGICs.…”
Section: Introductionmentioning
confidence: 99%